African Americans’ perspective on COVID-19 and influenza vaccines: A qualitative study - Marin Schmitt; Kelly W. Gagnon; Jennifer L. Walsh; Yuri Amirkhanian; Jeffrey A. Kelly; Katherine G. Quinn (Community Health Equity Research & Policy, 2026)
Purpose Annual vaccinations, such as influenza and COVID-19, are a safe and effective way of preventing disease and promoting healthier communities, yet many factors impact uptake. Black and African Americans face numerous barriers to vaccination, reflected in consistently lower vaccination rates and higher hospitalization and mortality rates. This qualitative study aimed to understand perceptions and factors influencing COVID-19 and influenza vaccination among Black and African American adults to inform interventions and outreach to prevent increased acuity of vaccination disparities. Eighty-six Black and African Americans in Milwaukee, WI were purposively recruited to participate in in-depth interviews. Major Findings We identified two themes and five subthemes reflecting vaccine perspectives, influences, and decision-making. In the first theme, similarities and differences in attitudes and willingness to get vaccinated against influenza and COVID-19, we identified three subthemes: (1) prevention was a motivating factor for getting both COVID-19 and influenza vaccines; (2) mistrust surrounding COVID-19 and the COVID-19 vaccine fueled hesitancy; and (3) some participants held discordant beliefs surrounding vaccines and healthcare. In the second theme, sources of vaccine information influencing vaccine perspectives , we identified two subthemes: (1) main sources of vaccine information were television news and the internet, not trusted healthcare professionals, and (2) life experiences affected perspectives. Conclusions Our findings show that vaccine perspectives are shaped by a complex interplay of personal beliefs, experiences, cultural identity, and trust. Public health strategies to improve vaccination rates should acknowledge mistrust, dispel myths and misinformation, and engage trusted communities and messengers across both healthcare and community settings.